Adopting lean thinking in performance administrative and cost for economic units - رائد مجيد عبد محمد; خليل ابراهيم اسماعيل (Journal of Madenat Alelem University College, 2019)
The aim of this study is to determine the extent to which used lean thinking is to achieve the objectives of industrial organizations, by reaching the possibility of applying the tools of lean thinking and relying on the house of lean thinking, and learning about the modern methods such as total quality management, lean manufacturing and just in time and continuous improvement, which aims To eliminate losses and reduce production time Reduce production costs and improve the performance of operations to achieve the wishes and needs of the customer and satisfaction, and for the purpose of this study was used descriptive analytical method by preparing a survey list distributed to some of my employees General Company for Electrical Industries and number (34) questionnaires were excluded identification number (4) not to answer accuracy by respondents, to become the final number of good analysis (30) questionnaires.